Effectiveness of Feature Extraction Techniques for Facial Identification - K. Minney Prisilla; N. Jayashri (International Journal of Computational and Experimental Science and Engineering, 2025)
Criminal activities and crime tenancy are increasing in the society when the technology and population increases. The process of identifying and determine criminals and avoiding them from involving in criminal activities are tedious task for police as well as public. Therefore, criminal tracking system is also needed to strengthen. Apart from traditional system, now a days the police and government is also implementing technology based tracking system for criminal identification. An efficient facial feature extraction algorithm and face identification algorithm are needed for this identification system. In this research, the performance of principal component analysis and local binary pattern algorithms are analysed with the support of convolutional neural network.